2016
DOI: 10.4103/0019-5413.193483
|View full text |Cite
|
Sign up to set email alerts
|

Results of neurolysis in established upper limb Volkmann’s ischemic contracture

Abstract: Background:Treatment of established cases of Volkmann's ischemic contracture (VIC) of upper limb is very tedious. Since the period of Volkmann, various experimental works are being performed for its treatment, but none are effective. Disabilities from nerve palsy and hand muscle paralysis are more problematic than any other deformity in VIC. To solve these problems, we conducted a study to see the result of neurolysis of median and ulnar nerve and their subcutaneous placement in established cases of VIC.Materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Sharma et al from India reported an age-range of 3-25 years, with 18 years as the average age at presentation. Meena et al 7 from Iran reported 8.3 years as the average age of their patients. 6 In this study, a significant proportion of patients developed VICs following their treatment for forearm fractures by traditional bone setters in the rural locales.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Sharma et al from India reported an age-range of 3-25 years, with 18 years as the average age at presentation. Meena et al 7 from Iran reported 8.3 years as the average age of their patients. 6 In this study, a significant proportion of patients developed VICs following their treatment for forearm fractures by traditional bone setters in the rural locales.…”
Section: Discussionmentioning
confidence: 96%
“…Sharma et al from India reported an age-range of 3-25 years, with 18 years as the average age at presentation. Meena et al 7 from Iran reported 8.3 years as the average age of their patients. 6 …”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations